Manipulating male fertility in barley (Hordeum vulgare L.) - Talle, Behzad (2017)
Formation of secondary wall thickening in the endothecium layer of anther is important for anther dehiscence and pollen release. In Arabidopsis this process has been shown to be regulated by R2R3-type MYB transcription factor MYB26 (Yang et al., 2007) and two NAC domain transcription factors, NAC Secondary Wall Promoting Factor 1 (NST1) and NST2 (Mitsuda et al., 2005). Characterisation of the regulation of endothecium development and anther dehiscence in agronomically important cereals such as barley will enable better understanding of pollen dispersal process in barley and other important crops. Moreover, in the longer term it may also facilitate identification of a stable sterile line for hybrid seed production in barley and potentially other cereals such as wheat. This project was aimed at identification and characterisation of the putative NST1 and NST2 orthologues in barley using reverse genetics approaches. The putative orthologous sequences in barley were identified by initially identifying the rice and Brachypodium putative sequences, prior to obtaining barley putative orthologues. The authenticity of the identified sequences was confirmed by comparison of their expression patterns and the level of synteny between Arabidopsis, rice, Brachypodium and barley sequences. These sequences were analysed by repression and overexpression in barley Golden Promise cultivar. SRDX repression of the putative sequences in barley resulted in reduction of fertility and associated reduction in plant height and spike size. The overexpression lines of HvNST1 and HvNST2 also showed reduction in fertility coupled with reduced spike size and plant height. Expression analysis in the barley transgenic lines suggested that the NST2 putative orthologue was regulated by NST1 and that MYB26 seemed to be upstream of these two genes. Further analysis is needed to confirm the nature of this interaction in barley. Moreover, this project explored the possibility of degradation of Arabidopsis Male Sterile 5 protein via the N-end rule proteolysis pathway. The preliminary results of this experiment suggested that the N-terminus of AtMS5 could be important in its degradation under in vitro conditions; however there needs to be further analyses to confirm this behaviour in vivo.